Attitudes, teacher strategies and achievement - Paulo A. Meyer M. Nascimento; Britta Kilian; Kevin Isaac (Universidade Federal de Juiz de Fora, 2020)
International evidence on the relationship between reading achievement and attitudes towards reading mostly shows a positive association between one and another. If that is the case, one could intuitively consider strategies adopted by teachers in the classroom as a way to motivate their students to read more and thus enhance their learning and boost student reading scores. This paper examines associations between students' attitudes towards reading, instructional strategies adopted by their teachers in the classroom, and reading achievement observed for the German sample at the 2006 edition of the Progress in International Reading Literacy Study - PIRLS 2006. Using internationally recognized large scale assessment data and relevant literature, the present article tests aspects of Walberg's model of chief productivity factors in school learning (REYNOLDS; WALBERG, 1992; WALBERG, 1981, 1986), in an attempt to draw some trends that might be useful for future research in Germany and abroad. The coming sections are structured as follows: section 2 highlights the relevant literature on student attitudes, teacher strategies and achievement, and the Walberg's model of educational productivity; section 3 presents the hypotheses to be tested, the databased to be used and the limitations of the present study; section 4 details the adopted multilevel model, its variables and results; section 5 concludes.